A proteomic analysis shows the stimulation of light reactions and inhibition of the Calvin cycle in the skin chloroplasts of ripe red grape berries - Teixeira, António; Noronha, Henrique; Sebastiana, Mónica; Fortes, Ana Margarida; Gerós, Hernâni (Frontiers in Plant Science, 2022)
The role of photosynthesis in fruits still challenges scientists. This is especially true in the case of mature grape berries of red varieties lined by an anthocyanin-enriched exocarp (skin) almost impermeable to gases. Although chlorophylls are degraded and replaced by carotenoids in several fruits, available evidence suggests that they may persist in red grapes at maturity. In the present study, chloroplasts were isolated from the skin of red grape berries (cv. Vinhão) to measure chlorophyll levels and the organelle proteome. The results showed that chloroplasts (and chlorophylls) are maintained in ripe berries masked by anthocyanin accumulation and that the proteome of chloroplasts from green and mature berries is distinct. Several proteins of the light reactions significantly accumulated in chloroplasts at the mature stage including those of light-harvesting complexes of photosystems I (PSI) and II (PSII), redox chain, and ATP synthase, while chloroplasts at the green stage accumulated more proteins involved in the Calvin cycle and the biosynthesis of amino acids, including precursors of secondary metabolism. Taken together, results suggest that although chloroplasts are more involved in biosynthetic reactions in green berries, at the mature stage, they may provide ATP for cell maintenance and metabolism or even O2 to feed the respiratory demand of inner tissues.